A New Class of Linear Canonical Wavelet Transform - Bivek Gupta; Amit K. Verma; Carlo Cattani (Journal of Applied and Computational Mechanics, 2024)
We define a new class of linear canonical wavelet transform (LCWT) and study its properties like inner product relation, reconstruction formula and also characterize its range. We obtain Donoho-Stark’s uncertainty principle for the LCWT and give a lower bound for the measure of its essential support. We also give the Shapiro’s mean dispersion theorem for the proposed LCWT.